Rice Epigenetic Pathways: Great Genetic Variation and Implication for Rapid Rice Breeding - Yuan Li; Erik Persson (Journal of Plant Genetics and Crop Research, 2018)
Rice, as one of the most important crops in the world, is facing an ever-accelerating challenge from climate change. Epigenetic modification with its substantially high epimutation rate and the possibility for some epigenetic variation to act as a heritable contributor to crop environmental adaptability may hold great potentials for rapid crop breeding. Epigenetic modification is controlled by epigenetic pathways, and mutations disturbing the epigenetic pathways may lead to significant epigenetic and/or genetic changes. This is especially true for rice, whose genome is rich in epigenetic modifications and transposable elements (TEs) that are generally epigenetically silenced. Here, in this paper, we first reviewed the pathways that establish, maintain and remove rice DNA methylation, which is the most well studied epigenetic marker, as well as the genes that are involved. We then discussed how TEs amplify the phenotypic impact of epigenetic changes that could be a result of epigenetic pathway disturbances. At last, we presented the enormous amount of rice genome data that are publically available, within which great genetic variation in the genes that are involved within the epigenetic pathways is embedded. This genetic variation awaits to be exploited for their potentials in generating a heritable source of variation for rapid environmental adaptation, which may hold tremendous importance for rice breeding in the face of climate change.
Keywords: DNA methylation pathway